Effect of exogenous glucose and abscisic acid on physiological and morphological performances of in vitro indica rice (Oryza sativa L. sp. indica) - Suriyan Cha-um (2018)
The aim of this research is to investigate on the osmolarity changes, sugar profiles, chlorophyll fluorescence and growth performances of indica rice cultured under exogenous glucose and abscisic acid (ABA). Osmolality in the root tissues of rice was positively related to increase glucose concentration in the media, while ABA application does not affected. Endogenous soluble sugars, sucrose, glucose and fructose in rice seedlings were slightly increased when exposure to glucose and ABA. High osmolality in glucose treated seedlings was negatively related to total chlorophyll concentration. Chlorophyll a, chlorophyll b and total carotenoid concentrations in the rice seedlings were significantly damaged by high glucose and ABA application in the media. The chlorophyll a, total chlorophyll and total carotenoid degradation in the leaf tissues was positively conelated to maximum quantum yield of PSII (Fv/Fm), quantum efficiency of photosystem II (ΦPSII) and non-photochemical quenching (NPQ), respectively. The low efficiency of light capture in photosystem II should be caused to low growth, in term of root length, plant height and dry matter. Induced water deficit or drought stress by exogenous glucose application and ABA treatment in this investigation would be further applied to drought tolerant screening in rice breeding program. © 2007 Academic Journals.